Cancer burden in Mexico: urgent challenges to be met - Eduardo Lazcano-Ponce; Alejandro Mohar-Betancourt; Abelardo Meneses-García; Mauricio Hernández-Ávila (Instituto Nacional de Salud Pública, 2016)
Primary prevention of cancer was initiated with the introduction of Hepatitis B vaccine in the 80's. However, in primary prevention of cancer at the worldwide level has been relatively recent. Intervention-action initiatives began at the global level in 2003 with the WHO Framework Convention on Tobacco Control, which was the first treaty negotiated under WHO guidance and as of today includes 168 countries. This negotiation, although innovative, was somewhat overdue, considering that the causal association between exposure to tobacco and elevated cancer incidence was established over 65 years ago. Vaccines against hepatitis and more recently human papilloma virus are other noteworthy developments in primary cancer prevention. As for secondary prevention, it has focused on early detection of cancer, especially among women, first with screening based on the Pap test and later other strategies for cervical cancer detection. For breast cancer, early detection strategies such as mammograms and clinical breast examination have been used for many years. However, today their impact on mortality for this cancer has come into question. In this context, in Mexico we face enormous challenges to provide an efficient organized social response to cancer prevention and control. This issue of Salud Pública de México on "Cancer burden in Mexico: urgent challenges to be met" is an effort to estimate in epidemiological terms the breadth and depth of the problem faced in Latin America and particularly in Mexico. The authors do this by describing the enormous population-level and clinical challenges which need to be faced in the short term.   DOI: http://dx.doi.org/10.21149/spm.v58i2.7778